Talking problems : studies of discursive construction - Buttny, Richard (SUNY series in communication studies., 2004)
"Using discursive constructionism and conversation analysis, Talking Problems examines how participants orient to, communicate about, and act toward events as problems. The book examines a series of problems, including teenage parenthood in high school, interpersonal and family relationships during therapy, and racism and interracial relations on a university campus. These problems are taken as joint constructions and the interest is in how participants' versions of events get heard, what unfolds as a consequence of this, how participants position themselves, and what social realities are thereby created."--Jacket